A Comprehensive Analysis of the Effect of SIRT1 Variation on the Risk of Schizophrenia and Depressive Symptoms - Wang, Dandan; Tang, Wei; Zhao, Junxiong; Fan, Weixing; Zhang, Yi; Zhang, Chen (Frontiers in Genetics, 2020)
Depressive symptoms could be listed as mutual manifestations of both schizophrenia and major depressive disorder (MDD). Our recent work has discovered a functional locus rs3758391 of SIRT1 involved in MDD etiology. In this study, we hypothesized that SIRT1 SNP rs3758391 may be a risk factor for schizophrenia pathogenesis and its depressive symptoms. We recruited 715 schizophrenia patients and 723 healthy controls, and the psychotic and depressive symptoms were evaluated by PANSS and CDSS. 45.6% of schizophrenia patients had depressive symptoms. Schizophrenia patients with depression have lower levels of SIRT1 mRNA than those without depression (P＜0.01). There is a significant difference in the CDSS scores among the rs3758391 genotypes in schizophrenia patients (P＜0.01). Post-hoc comparisons showed that rs3758391 C/C and C/T carriers had higher CDSS scores than those with T/T carriers (Ps＜0.01). Our eQTL analysis showed a significant association between the rs3758391 and SIRT1 mRNA expression in the occipital cortex (P=0.003, P=0.03 after Bonferroni correction). Our preliminary findings provided suggestive evidence for SIRT1 conferring susceptibility to depressive symptoms in schizophrenia. SNP rs3758391 functionally affects the severity of depressive symptoms in schizophrenia patients. This SNP may be a biomarker for depression in schizophrenia.